Phenomenology of Terrorism: "Masks" and Crimes - NIKOLAEVNA, SHELSHAKOVA NATALIA (The journal of contemporary issues in business and government, 2021)
In history, many mistakes were made, such as: wars, distortion of history, trust in the first persons who wore "masks". You can shift the responsibility to politicians, the TV industry, and so on. If a number of conditions are met, a citizen can independently perform an analysis of the safety of their own life. To do this, you need to carefully look at the people around you (at home, at work, in the yard); conduct an objective analysis of negative news from TV and the Internet; analyze the activities of your immediate supervisor, whom you see weekly; analysis of the work of the educational institution where children study; the environmental situation in the city; the quality of life in terms of determining psychological health. Based on these factors, without being an expert in the field of security, a citizen will be able to draw conclusions about the legality of actions taken by the state against himself and his family. Based on the urgency of the problem, the article will present the types of crimes committed against citizens in "democratic" states.